IMPLIKASI KEKOSONGAN HUKUM TERHADAP KECERDASAN BUATAN SEBAGAI PELANGGAR KEKAYAAN INTELEKTUAL TERHADAP KARYA DIGITAL - Yonathan Ariel Alexander Tambunan; Dewa Ayu Dian Sawitri (Kertha Wicara: Journal Ilmu Hukum, 2025)
This study aims to comprehensively evaluate the implications of legal gaps regarding artificial intelligence (AI) as a potential infringement of intellectual property rights in the context of digital works in Indonesia, and to identify and analyze the need for revisions to Indonesia's Copyright Law to accommodate AI developments. Employing a normative juridical research method, this study utilizes statute, conceptual, and analytical approaches to examine relevant legislation, legal concepts, and critically analyze the implications of legal gaps. The research relies on primary legal materials such as copyright legislation, secondary legal materials including books and scholarly articles, and tertiary legal materials. The study finds that the current legal vacuum poses significant risks to intellectual property protection, potentially hampering innovation and creative industry growth. It also identifies crucial areas for legislative reform to address AI-generated works within the copyright framework. This study contributes to the development of a more comprehensive legal framework for protecting intellectual property rights in the AI era, offering concrete recommendations for Copyright Law revision.